Carotene Synthesis Changes of Rhodotorula Aurantiaca Indicator Yeasts in the Presence of Copper (II) Salts - Krystyna Krupiei; Hlib Kravchenko (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
Rhodotorula aurantiaca yeasts are ubiquitous microorganisms found in water, soil, plants, etc. Since the main requirement of an indicator organism is the wide occurrence in nature, this species can be an informative bioindicator of the ecological state of the environment. The aim was to study the influence of Cu (II) compounds on the color of carotenoid pigments intensity of two Rh. aurantiaca strains (Y-1193 and Y-1195).